Effect of body mass and midsole hardness on kinetic and perceptual variables during basketball landing manoeuvres - Nin, D. Z.; Lam, W. K.; Kong, P. W. (Journal of Sports Sciences, 2016)
This study investigated the effects of body mass and shoe midsole hardness on kinetic and perceptual variables during the performance of three basketball movements: (1) the first and landing steps of layup, (2) shot-blocking landing and (3) drop landing. Thirty male basketball players, assigned into "heavy" (n = 15, mass 82.7 ± 4.3 kg) or "light" (n = 15, mass 63.1 ± 2.8 kg) groups, performed five trials of each movement in three identical shoes of varying midsole hardness (soft, medium, hard). Vertical ground reaction force (VGRF) during landing was sampled using multiple wooden-top force plates. Perceptual responses on five variables (forefoot cushioning, rearfoot cushioning, forefoot stability, rearfoot stability and overall comfort) were rated after each movement condition using a 150-mm Visual Analogue Scale (VAS). A mixed factorial analysis of variance (ANOVA) (Body Mass × Shoe) was applied to all kinetic and perceptual variables. During the first step of the layup, the loading rate associated with rearfoot contact was 40.7% higher in the "heavy" than "light" groups (P = .014) and 12.4% higher in hard compared with soft shoes (P = .011). Forefoot peak VGRF in a soft shoe was higher (P = .011) than in a hard shoe during shot-block landing. Both "heavy" and "light" groups preferred softer to harder shoes. Overall, body mass had little effect on kinetic or perceptual variables.